Corporate responsibility of the banking business as the basis of the financial stability of the banking sector - Ma Yigao (Kharkiv : V. N. Karazin Kharkiv national university, 2024)
Object of research banking system. Subject of research is corporate responsibility of the banking business. As the core of the financial industry, commercial banks not only play a vital role in the development of social economy and the adjustment of industrial structure but also shoulder social responsibilities. Therefore, in the new economic situation, commercial banks should not only pay attention to profit but also accept the constraints of social responsibility system. With the promulgation of a series of relevant policies such as the Guidelines on Corporate Social Responsibility of Financial Institutions in China's Banking Sector, more and more commercial banks have begun to pay attention to and consciously undertake social responsibility, which is conducive to improving corporate image and enhancing social service capabilities.
Корпоративна відповідальність банківського бізнесу як основа фінансової стабільності банківського сектору
Scientific advisor: Galych Roman, PhD of law, associate professor, department banking business and financial technologies
Keywords: SOCIAL SCIENCES::Business and economics::Economics; financial technology; state-owned; banks; social responsibility; financial stability